2010
DOI: 10.1158/0008-5472.can-09-1530
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Hormone-Dependent Breast Cancers: Implications of the Presence of Dysfunctional Transcriptional Networks Activated by Insulin via the Immune Transcription Factor T-bet

Abstract: Estrogen receptor α (ERα)-positive breast cancers that co-express transcription factors GATA-3 and FOXA1 have a favorable prognosis. These transcription factors form an autoregulatory hormonal network that influences estrogen responsiveness and sensitivity to hormonal therapy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The context dependency of this interaction must be further explored to unravel the molecular mechanisms by which CTCF enhances or impedes binding of FOXA1 to DNA. The interplay between FOXA1 and ER may extend beyond the ability of FOXA1 to control ER expression and activity. Although these results suggest a positive regulatory loop between ER and FOXA1 ( Figure 2B), others have described FOXA1 to be down-regulated with oestrogen treatment [128,[156][157][158]. Providing support for FOXA1 being an ER target, a more recent analysis of the ER chromatin interaction network revealed that ER-binding sites flank the FOXA1 gene [155].…”
Section: Foxa1 Expression In Breast Cancermentioning
confidence: 94%
“…The context dependency of this interaction must be further explored to unravel the molecular mechanisms by which CTCF enhances or impedes binding of FOXA1 to DNA. The interplay between FOXA1 and ER may extend beyond the ability of FOXA1 to control ER expression and activity. Although these results suggest a positive regulatory loop between ER and FOXA1 ( Figure 2B), others have described FOXA1 to be down-regulated with oestrogen treatment [128,[156][157][158]. Providing support for FOXA1 being an ER target, a more recent analysis of the ER chromatin interaction network revealed that ER-binding sites flank the FOXA1 gene [155].…”
Section: Foxa1 Expression In Breast Cancermentioning
confidence: 94%
“…The ER-positive MCF-7 breast cancer cell was noted to have increased T-bet activity associated with insulin exposure, which also was associated with tamoxifen-resistance [170]. Feng and colleagues furthered this understanding by noting that ER signaling was positively associated with WHSC1, a histone methyltransferase recruited to the ERα gene by BET proteins.…”
Section: Treatment Options In Ar+ Breast Cancermentioning
confidence: 99%
“…These transcription factors constitute a cell lineage-specific network that affects estrogen responsiveness as well as sensitivity to hormonal therapy. Despite the role of the ERdriven signaling cascade in the development of antiestrogen resistance, it is increasingly recognized that disruption of the ER/GATA-3/FOXA1 network represents an alternative way for breast cancer cells to acquire resistance to currently applied hormonal treatments (27). In addition, activation of other networks affects other cell types within the tumor microenvironment and contributes to tumor progression and metastasis (e.g., β-catenin/cAMP responsive element binding [CREB]-binding protein [CBP], chemokine receptors, retinoic acid receptors and many others) (28)(29)(30)(31)(32).…”
Section: O V E M B E R -D E C E M B E R 2 0 1 1 T R a N S C R I P T Imentioning
confidence: 99%